A longitudinal assessment of occupational stress in Emergency Department Nursing Staff. (22nd January 2020) - Basu, Subhashis; Harris, Angela; Mason, Sue; Norman, Joseph
Abstract: Aims: To examine perceptions of occupational stress in Emergency Department (ED) nurses and measure the impact of interventions to address them. Background: Cross‐sectional studies internationally have established that Emergency Department (ED) nursing staff experience high levels of occupational stress. Few however have examined changes in perceptions of stress over time or the impact of interventions to address them. Evaluation: A structured questionnaire completed by volunteer nursing staff in one United Kingdom ED assessing perceptions of occupational stress and job satisfaction. Questionnaire rounds were administered in 2014 (T1), 2015 (T2) and 2017 (T3) at 18‐month intervals. Statistical analyses were conducted using multivariate regression, t ‐tests and Mann–Whitney U tests. Key Issue: Statistically significant improvements in effort‐reward balance, relational justice and job satisfaction were seen between T2 and T3 for nurses completing questionnaires at all three time points, but not for other stressors. Conclusion: This study suggests that organisational interventions, supported by robust research data and consistent departmental leadership can positively influence perceptions of organisational stress in ED nurses. Our approach is generic, internationally applicable and can be adopted in all EDs. Implications of nursing management: These occupational stressors are common to all EDs. Nurse managers should know their distribution amongst their staff. Such data can inform interventions to achieve maximal benefits for staff wellbeing and may be of value when targeting resources in times of financial pressure.